Implementasi Kebijakan Dispensasi Nikah Sebagai Tantangan Struktural Terhadap Pemberdayaan Perempuan Untuk Mewujudkan SDGs Nomor 5 - Islami, Diajeng Dhea Annisa Aura; Wulandari, Diah Ayu; Sapanah, Mawar; Amelia, Dean Putri; Ramadhani, Dwi Aryanti (Esensi Hukum, 2025)
This study critically examines the implementation of marriage dispensation policies in Indonesia and their implications for women's empowerment, particularly in the context of achieving Sustainable Development Goal (SDG) 5 and its target 5.3, which emphasizes the elimination of child marriage. Although Indonesia revised the minimum legal age of marriage to 19 for both men and women through Law No. 16 of 2019, the continued application of marriage dispensations, as permitted under Article 7(2) of the Marriage Law and further regulated by Supreme Court Regulation No. 5 of 2019, still legitimizes early marriage based on the broadly interpreted notion of "urgent necessity." Employing a normative juridical methodology, this study utilizes secondary data comprising statutory regulations, legal doctrines, judicial decisions, and relevant international instruments. This analysis is further supported by an empirical case study involving the marriage of two junior high school students in Pemalang Regency, which illustrates the real-world implications of these policies. The findings reveal that legal ambiguities and insufficient oversight within the dispensation framework perpetuate the practice of child marriage, thereby restricting girls’ access to education, healthcare, and economic opportunities. Using a feminist legal approach and a child rights-based perspective, this study underscores the urgent need for legal reform, gender-responsive policy development, and cross-sectoral collaboration to eliminate child marriage. The study contributes to strengthening Indonesia's national legal framework in fulfilling its global commitment to achieving a gender-equitable development agenda.